Timing and development of sedimentation of the Cleaverville Formation and a post‐accretion pull‐apart system in the Cleaverville area, coastal Pilbara Terrane, Pilbara, Western Australia. (15th September 2019) - Kiyokawa, Shoichi; Aihara, Yuhei; Takehara, Mami; Horie, Kenji
Abstract: In the Cleaverville area of Western Australia, the Regal, Dixon Island, and Cleaverville Formations preserve a Mesoarchean lower‐greenschist‐facies volcano‐sedimentary succession in the coastal Pilbara Terrane. These formations are distributed in a rhomboidal‐shaped area and are unconformably overlain by two narrowly distributed shallow‐marine sedimentary sequences: the Sixty‐Six Hill and Forty‐Four Hill Members of the Lizard Hills Formation. The former member is preserved within the core of the Cleaverville Syncline and the latter formed along the northeast‐trending Eighty‐Seven Fault. Based on the metamorphic grade and structures, two deformation events are recognized: D1 resulted in folding caused by a collisional event, and D2 resulted in regional sinistral strike‐slip deformation. A previous study reported that the Cleaverville Formation was deposited at 3020 Ma, after the Prinsep Orogeny (3070–3050 Ma). Our SHRIMP U–Pb zircon ages show that: (i) graded volcaniclastic–felsic tuff within the black shale sequence below the banded iron formation in the Cleaverville Formation yields an age of (3 114 ±14) Ma; (ii) the youngest zircons in sandstones of the Sixty‐Six Hill Member, which unconformably overlies pillow basalt of the Regal Formation, yield ages of 3090–3060 Ma; and (iii) zircons in sandstones of the Forty‐Four Hill Member show two age peaks at 3270 Ma and 3020 Ma. In this way, the Cleaverville Formation was deposited at 3114–3060 Ma and was deformed at 3070–3050 Ma (D1 ). Depositional age of the Cleaverville Formation is at least 40–90 Myr older than that proposed in previous studies and pre‐dates the Prinsep Orogeny (3070–3050 Ma). After 3020 Ma, D2 resulted in the formation of a regional strike‐slip pull‐apart basin in the Cleaverville area. The lower‐greenschist‐facies volcano‐sedimentary rocks are distributed only within this basin structure. This strike‐slip deformation was synchronous with crustal‐scale sinistral shear deformation (3000–2930 Ma) in the Pilbara region. Abstract : The Cleaverville Formation of Pilbara Greenstone belt yields an age of (3114 ±14) Ma from graded volcaniclastics–felsic tuff within the black shale sequence below the banded iron formation. Youngest zircons in sandstones of the Sixty‐Six Hill Member, which unconformably overlies pillow basalt of Regal Formation, yield ages of 3090–3060 Ma and the zircons in sandstones of the Forty‐Four Hill Member show two age peaks at 3270 Ma and 3020 Ma. Sinistral trike‐slip pull‐apart basin is formed at the Cleaverville area during cratonization of the West Pilbara area. Abstract : クリバービル層は西オーストラリア・ピルバラクラトンにある中太古代のグリーンストン帯中の海洋起源の地層である. 特にその中に含まれる縞状鉄鉱層は，西ピルバラ地塊と東ピルバラ地塊が衝突したプリンセップ造山運動(3 070 3 050 Ma)以降に堆積したとされ，ピルバラ全域の層序を対比する上で重要な地層である. しかし，詳細な構造・層序復元･U‐Pb年代測定により，クリバーベル層は，3 100 Maごろに堆積したことが明らかになった. また，クリバービル地域からは，浅海堆積層(リザードヒルズ層；66ヒル/44ヒル部層)が確認され，これらの地層は海洋性島弧の付加衝突作用(3 070–3 050 Ma)時の堆積盆とその後の広域横ずれ運動(3 000–2 930 Ma)によるプルアパート堆積盆の形成を反映する. 本地域では，浅海性堆積物は大半が侵食され，褶曲軸部･断層沿いのみ分布し，堆積盆の基盤である31–32億年前の低変成度のグリーンストーン帯が露出する.